Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0251966
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of deep vein thrombosis through an ultrasound surveillance protocol in patients with COVID-19 pneumonia in non-ICU setting: A multicenter prospective study

Abstract: Objective The aim of this study was to assess the incidence of deep vein thrombosis (DVT) of the lower limbs, using serial compression ultrasound (CUS) surveillance, in acutely ill patients with COVID-19 pneumonia admitted to a non-ICU setting. Methods Multicenter, prospective study of patients with COVID-19 pneumonia admitted to Internal Medicine units. All patients were screened for DVT of the lower limbs with serial CUS. Anticoagulation was defined as: low dose (enoxaparin 20–40 mg/day or fondaparinux 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Our results and opinion are in line with Pieralli et al [ 17 ], that suggested a surveillance protocol by serial CUS to identify patients with DVT, helping its detection and avoiding its possible consequences.…”
Section: Discussionsupporting
confidence: 92%
“…Our results and opinion are in line with Pieralli et al [ 17 ], that suggested a surveillance protocol by serial CUS to identify patients with DVT, helping its detection and avoiding its possible consequences.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 Even while on anticoagulation patients develop TEs. 25,26 We have observed that 79% of our patients had a hypercoagulable TEG tracing at the time of admission and 30.23% (13/43) had a documented TE during ICU stay even when they were on therapeutic doses of anticoagulants. The high incidence of TE in CAC might be due to the widespread inflammation and severity of the infection which in turn causes widespread clot formation.…”
Section: Resultsmentioning
confidence: 69%
“…The cumulative incidence of TE in COVID‐19 patients admitted to ICU is around 30% and systemic anticoagulation has been recommended to patients requiring ICU admission 7,8 . Even while on anticoagulation patients develop TEs 25,26 . We have observed that 79% of our patients had a hypercoagulable TEG tracing at the time of admission and 30.23% (13/43) had a documented TE during ICU stay even when they were on therapeutic doses of anticoagulants.…”
Section: Discussionmentioning
confidence: 68%
“…However, in seven out of eight cases, it was only a distal DVT giving an incidence of proximal DVT of 2.3%. More recent studies confirm the low prevalence of asymptomatic proximal DVT [ 13 , 14 ]. In conclusion, all besides one study showed a low incidence of proximal DVT outside the ICU.…”
Section: Discussionmentioning
confidence: 80%